Salt-activated bimetal–phenolic nanoadhesive for broad-spectrum micro- and nanoplastic removal across salinity gradients - Zheng Cai; Qingfeng Yao; Lan Zhao; Yan Cao; Yishuang Li; Xianluo Hu; Jingming Gong (Chemical Engineering Journal, 2026)

Spatial and temporal evolution of the groundwater depth and indirect effects during the spring irrigation period in the Hetao Irrigation District - Yi Zhao; Haibin Shi; Xianyue Li; Shuya Yang; Haoqi Han; Yunlei Dong; Qingfeng Miao; Jianwen Yan; Cong Hou; Xu Dou (Irrigation Science, 2026)

SfIML-1 interacts with integrin β5 to mediate fungal conidial adhesion and immune activation in Spodoptera frugiperda - Fang-Fang Liu; Qi-Gui Gao; Yue Sun; Chao-Peng Liang; Hai-Yan Ren; Qingfeng Tang; Liang Wen; Bang-Xian Zhang; Xiang-Jun Rao (Pesticide Biochemistry and Physiology, 2026)

Inferring irrigation regimes and sunshine duration from the distribution and spectral characteristics of farmland microplastics - Hangzheng Zhao; Xu Han; Changming Cao; Ziyi Zan; Bo-Tao Zhang; Jiamin Wang; Qingfeng Tang; Weifeng Yue; Yan Liu (Environmental Pollution, 2026)

Optimization of fertilization regimes for major crops in the Hetao Irrigation District based on the DNDC model and evaluation of economic benefits - Cong Hou; Haibin Shi; Yan Yan; Qingfeng Miao; Yi Zhao; Sihan Xue; Jiapeng Zhang; Weiping Li (European Journal of Agronomy, 2026)

Seismic behaviours of T-shaped steel-concrete-steel sandwich composite walls under different axial compression ratios - Qingfeng Liu; Tao Wang; Jia-Bao Yan (Engineering Structures, 2026)

Cyclo(Gly-Tyr) alleviates hypercholesterolemia via modulating gut microbiota: critical roles and mechanisms of Bacteroides and Akkermansia - Jingzhi Chen; Zikang Li; Xinhong Wang; Xinyi Li; Manru Chen; Yan Hua; Ziren Su; Jiannan Chen; Qingfeng Xie; Yucui Li (Food Research International, 2026)

MnO2-resistant ABTS spectrophotometry for trace permanganate - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Xuewei Yu; Bo Sun; Zhongda Yan; Haoqiang Tan; Qingfeng Cheng; Jun Ma (ENGINEERING Environment, 2026)

Research on vertical ecological compensation mechanism based on ecosystem services supply-demand balance—A case study of the Nine Plateau Lakes in Yunnan Province - Jianjun Sheng; Qingfeng Xiao; Zhanpeng Du; Qin Zhang; Yan liu; Yinglan Xue (Environment, Development and Sustainability, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

Impact performance of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wenli Chen; Zaixian Chen; Wei Li; Yun Niu; Zhaolong Li (Ocean Engineering, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Experimental and numerical study on ice-induced vibration control of jacket-type offshore wind turbine using tuned mass damper - Rui Wang; Jigang Zhang; Zhehao Ma; Qingfeng Yan; Feifei Liu; Zaixian Chen; Wei Li; Yun Niu (Ocean Engineering, 2026)

Seismic behaviour of H-shaped steel-concrete-steel composite walls with innovative C-channel connectors to enhance resilience - Jin Wang; Yan Lu; Qingfeng Liu (Engineering Structures, 2026)

Efficient removal of Pb2+ by iron-doped hydroxyapatite: Synthesis, adsorption, kinetics and mechanisms - Yan Li; Yuxia Zhong; Hang Lei; Qingfeng He; Fengchu Liao; Sisi Tang; Mengdi Liu; Yue-Fei Zhang (Environmental Research, 2025)

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Corrigendum to “Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation” [Toxicology and Applied Pharmacology, 499 (2025) 117352] - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

Vibration damping and finite element analysis of a 10 MW jacket-type offshore wind turbine - Jigang Zhang; Haodong Sui; Zhehao Ma; Wenli Chen; Qingfeng Yan; Wei Li; Hongjian Xu; Fengbo Yu; Yun Niu; Junxian Zhao (Ocean Engineering, 2025)

Solubility and mass transfer of hydrogen in light cycle oil and vacuum gas oil - Tao Jiang; Fei Yu; Hanfei Shen; Yan Yan; Qingfeng Tan; Chunming Xu; Zhentao Chen (Fuel, 2025)

A novel montmorillonite-based room temperature phosphorescence material by host-guest system - Yan Zou; Junjie Ding; Libing Liao; Qingfeng Guo; Pengfei Shuai (Applied Clay Science, 2025)

Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Structural performance and design of assembled aluminum alloy-concrete-carbon steel double-skin tubular column - Wengang Xu; Jigang Zhang; Qingfeng Yan; Wei Li; Zhenhui Song; Fengbo Yu; Yun Niu; Hanyu Song (Ocean Engineering, 2025)

Microbial community and dynamic changes of extracellular polymeric substances in relation to plastisphere of disposable surgical masks in natural aquatic environment - Ling Zhang; Yuxin Zhou; Zixian Zhu; Feifei Yan; Luxi Tan; Chunyan Wei; Zihao Wang; Qingfeng Chen; Ying Zhang (Journal of Oceanology and Limnology, 2025)

Study on Impact Tendency and Damage Characteristics of Rock-Like Materials Based on Acoustic and Thermal Responses - Shoujian Peng; Yan Yang; Qingfeng Xu; Jiang Xu; Chaolong Qin; Xiaoli Nong (Rock Mechanics and Rock Engineering, 2024)

Recent progress in carbonaceous materials for the hydrogen cycle: Electrolytic water splitting, hydrogen storage and fuel cells - Guanghui Xia; Habibullah; Qingfeng Xie; Qin Huang; Meitong Ye; Bingshou Gong; Rui Du; Yao Wang; Yigang Yan; Yungui Chen; Chaoling Wu (Chemical Engineering Journal, 2024)

Global Trends and Networks in Soil Fertility Enhancement Techniques: a Bibliometric Analysis - Zhuangzhuang Feng; Qingfeng Miao; Haibin Shi; Xianyue Li; Jianwen Yan; José Manuel Gonçalves; Dandan Yu; Yan Yan; Weiying Feng (Journal of Soil Science and Plant Nutrition, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Irrigation scheduling in sand-layered farmland: Evaluation of water and salinity dynamics in the soil by SALTMED-1D model under mulched maize production in Hetao Irrigation District, China - Zhuangzhuang Feng; Qingfeng Miao; Haibin Shi; Xianyue Li; Jianwen Yan; José Manuel Gonçalves; Liping Dai; Weiying Feng (European Journal of Agronomy, 2024)

Study on green closed-loop regeneration of waste lithium iron phosphate based on oxalic acid system - Xiaolong Chai; Xiaohua Yu; Qingfeng Shen; Xingbin Li; Yan Lin; Weisong Cai; Ya Yuan (Waste Management, 2024)

LncFASA promotes cancer ferroptosis via modulating PRDX1 phase separation - Xiao Fan; Fangzhou Liu; Xiang Wang; Ying Wang; Yu Chen; Chengyu Shi; Xinwan Su; Manman Tan; Qingfeng Yan; Jinrong Peng; Jianzhong Shao; Yan Xiong; et al. (Science China Life Sciences, 2024)

Estimation of the Relative Chlorophyll Content of Carya illinoensis Leaves Using Fractional Order Derivative of Leaf and Canopy Scale Hyperspectral Data - Jiajia Xu; Genshen Fu; Lipeng Yan; Lei Yu; Fan Kuang; Qingfeng Huang; Xuehai Tang (Journal of Soil Science and Plant Nutrition, 2024)
Chlorophyll is a crucial physiological and biochemical indicator that impacts plant photosynthesis, accumulation of photosynthetic products, and final yield. The measurement and analysis of chlorophyll content in plants can provide valuable insights into their nutritional status and overall health. The non-destructive and efficient estimation of relevant plant physiological and biochemical indicators using hyperspectral technology can provide a reliable method for collecting data on nutrient levels and health status during plant growth and development. Fifty-three Carya illinoensis plants of Jiande and Changlin series known for their exceptional qualities and significant economic benefits were used as the research object for collecting their leaf and canopy hyperspectral data. Firstly, fractional order derivative (FOD) was used for spectral preprocessing. Secondly, the spectral response relationship between spectrum and relative chlorophyll content (soil and plant analyzer development, SPAD) was explored by combining single-band and two-band spectral index (normalized difference spectral index, NDSI). The correlation coefficient of Pearson correlation analysis was used to estimate the linear correlation between variables. Finally, the correlation between the spectral feature variables and SPAD was analyzed and calculated. Top 10 absolute values of the correlation coefficients were screened out as modeling variables. eXtreme gradient boosting (XGBoost) machine learning algorithm was used to construct the optimal estimation model of SPAD of Carya illinoensis leaves. Results showed that the correlation between leaf and canopy spectrum after FOD pretreatment and SPAD was substantially improved, compared with raw spectrum. FOD combined with leaf and canopy NDSI was more effective than single band in improving the correlation between spectral characteristics and target components, which was increased by 0.166 and 0.338, respectively. The leaf spectrum could estimate SPAD more accurately than that of canopy spectrum. The optimal SPAD model was the 0.5th-order derivative transformation combined with two-band leaf spectral index (NDSI) model. The R 2 P was 0.788, and the RMSEP was 0.842 in prediction set. On one hand, this study confirms the feasibility of rapid and non-destructive estimation of SPAD of Carya illinoensis leaves using hyperspectral technology. On the other hand, FOD combined with two-band spectral indices can significantly improve the response relationship between spectral characteristics and target variables, enrich hyperspectral data processing methods, and propose a novel approach for the detection of plant nutrient level and health.

Theoretical investigation of outer-sphere adsorption of hydrated yttrium ion on the basal surfaces of kaolinite: A density functional study - Bing Li; Xuefa Shi; Chuanshun Li; Qingfeng Hua; Xinfang Li; Quanshu Yan (Chemical Geology, 2023)

Enhancement of electrocatalytic activity for micropollutant removal by CeO2@CNT-based membranes: The influences of the structure and morphology of CeO2 - Yongbao Chu; Qingfeng Ma; Xuan Hou; Yunxin Zhang; Jingyi Zhang; Xiaoyu Ni; Yan Wang (Journal of Cleaner Production, 2023)

The hind information: Exploring the impact of physical damage on mask microbial composition in the aquatic environment - Hu Wang; Zixian Zhu; Ling Zhang; Xiaohui Liu; Weihong Sun; Feifei Yan; Yuxin Zhou; Zhi Wang; Xiaofeng Wang; Chunyan Wei; Jie Lai; Qingfeng Chen; et al. (Environmental Research, 2023)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

Water replenishment to maize under heat stress improves canopy temperature and grain filling traits during the reproductive stage - Xinglong Wang; Ning Luo; Yupeng Zhu; Ye Yan; Haijiang Wang; Hejing Xie; Pu Wang; Qingfeng Meng (Agricultural and Forest Meteorology, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

Circ_0060937 Contributes to the Development of Lung Cancer via Positively Regulating LAD1 Expression by Binding to miR-1304-5p - Dubiao Xian; Yuanyuan Wu; Wenhui Chen; Qingfeng Yan; Yuechang Wu (Biochemical Genetics, 2023)

Effects of load-related parameters on the dynamic response of concrete-filled double-skin steel tube K-joints under lateral impact loading - Qingfeng Yan; Jigang Zhang; Zhehao Ma; Feifei Liu; Guoliang Zhao; Chi Gu; Hanyu Song; Weicheng Zhang (Ocean Engineering, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

High fructose-induced skeletal muscle insulin resistance could be alleviated by berberine via AMPD1 and ADSL - Juanjuan Cheng; Xingdong Ma; Guangtao Yan; Qiuxia Yu; Zhen Huang; Guoshu Lin; Mengyao Li; Fengkun Guan; Ziren Su; Fang Yan; Yuhong Liu; Qingfeng Xie (Food and Chemical Toxicology, 2023)

Experimental and numerical study on the dynamic behavior of concrete-filled double steel tubular T-joint under impact loading - Qingfeng Yan; Jigang Zhang; Feifei Liu; Zhehao Ma; Guoliang Zhao; Chi Gu; Hanyu Song; Yang Zhao (Ocean Engineering, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

CeO2 modified carbon nanotube electrified membrane for the removal of antibiotics - Qingfeng Ma; Yongbao Chu; Xiaoyu Ni; Jingyi Zhang; Haoze Chen; Fei Xu; Yan Wang (Chemosphere, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

Hemipilia yajiangensis (Orchidoideae, Orchidaceae), a new species from western Sichuan, China, based on molecular and morphological evidence - Jiaxin Yang; Shuai Peng; Junjie Wang; Yan Wang; Shixiong Ding; Jing Tian; Guangwan Hu; Qingfeng Wang (Kew Bulletin, 2022)

Effect of the presence of various natural organic matters on anodic oxidation of electrified carbon nanotube membrane - Yongbao Chu; Yingxin Li; Xiaoyu Ni; Jinhui Du; Qingfeng Ma; Min Wang; Yan Wang (Environmental Science and Pollution Research, 2022)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Soil and ambient air mercury as an indicator of coal-fired power plant emissions: a case study in North China - Zhonggen Li; Xufeng Chen; Wenli Liu; Taishan Li; Guangle Qiu; Haiyu Yan; Mingmeng Wang; Ji Chen; Guangyi Sun; Qingfeng Wang; Xinbin Feng (Environmental Science and Pollution Research, 2021)

Isolation and characterization of a recombinant Muscovy duck parvovirus circulating in Muscovy ducks in South China - Hanqin Shen; Jianfei Huang; Zhuanqiang Yan; Lijuan Yin; Qunhui Li; Qingfeng Zhou; Feng Chen (Archives of Virology, 2020)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Distribution of water-stable aggregates under soil tillage practices in a black soil hillslope cropland in Northeast China - Lei Yan; Xuexin Jiang; Xiaonan Ji; Liting Zhou; Siying Li; Chen Chen; Peiye Li; Yuanchen Zhu; Tianhao Dong; Qingfeng Meng (Journal of Soils and Sediments, 2020)

Assessing impacts of climate change on habitat suitability of Coregonus ussuriensis and other coldwater fishes in northern China - Baoxiu Xing; He Chen; Qingfeng Chen; Yan Zhang; Zifang Liu; Zhao Yang (Environmental Science and Pollution Research, 2019)

Marker-assisted backcrossing of lcyE for enhancement of proA in sweet corn - Ruichun Yang; Zhiguang Yan; Qingfeng Wang; Xiaoqin Li; Faqiang Feng (Euphytica, 2018)

Assessment of macrophyte, heavy metal, and nutrient concentrations in the water of the Nairobi River, Kenya - Samwel Maina Njuguna; Xue Yan; Robert Wahiti Gituru; Qingfeng Wang; Jun Wang (Environmental Monitoring and Assessment, 2017)

Preliminary studies of multi-micro/nanomaterials immobilized on the bamboo timber surface - Chunde Jin; Jingpeng Li; Jin Wang; Huanhuan Zheng; Qingfeng Sun; Shenjie Han; Chenye Yan; Qiufang Yao; Bitao Fan (Journal of the Indian Academy of Wood Science, 2016)

Sulfur- and lead-isotope geochemistry of the Balugou Cu-Pb-Zn skarn deposit in the Wulonggou area in the eastern Kunlun Orogen, NW China - Qingfeng Ding; Wei Yan; Benlong Zhang (Journal of Earth Science, 2016)

Cystic olfactory ensheathing cell tumor: a case report - Xuchen Qi; Yingfeng Wan; Qingfeng Yan; Yirong Wang; Shuxu Yang (Acta Neurologica Belgica, 2015)

QTL mapping for the tocopherols at milk stage of kernel development in sweet corn - Faqiang Feng; Feng Deng; Peng Zhou; Jianbin Yan; Qingfeng Wang; Ruichun Yang; Xiaoqin Li (Euphytica, 2013)

Holocene vegetational and climatic variation in westerly-dominated areas of Central Asia inferred from the Sayram Lake in northern Xinjiang, China - QingFeng Jiang; JunFeng Ji; Ji Shen; Ryo Matsumoto; GuoBang Tong; Peng Qian; XueMei Ren; DeZhi Yan (Science China Earth Sciences, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

A comparison of different optimization algorithms for retrieving aerosol optical depths from satellite data: an example of using a dual-angle algorithm - Xihan Mu; Qingfeng Shen; Zhao-Liang Li; Guangjian Yan; José Antonio Sobrino (International Journal of Remote Sensing, 2011)